Multilingualism - A New Aspect of Teachers' Professional Development - Katica Pevec Semec; Saša Jazbec (University of Maribor Press, 2018)
Multilingualism is an important element in the life of modern people, and a relevant topic of professional, scientific and political discussion. This paper will shed light on theoretical aspects of multilingualism: past and present concepts of multilingualism, the advocacy for and the promotion of multilingualism in the EU, as well as multilingualism in educational discourse, and teachers' professional development. The next section focuses on a project that puts multilingualism into practice in a creative manner and can thus be seen as a role model in this field of work. The paper pays special attention to the teachers who work within the framework of multilingualism, and to their new roles, distinctly different from the traditional teacher role. The concept of multilingualism as established and realized by the project covers multilingualism at the border of three countries, three languages and three educational systems and could be used as a model for other similar practices.